Islamic Education and Capitalism: Modern Islamic Education Management in Banten - Ahmad Qurtubi; A. Asari (PT ARRUS Intelektual Indonesia, 2022)
Abstract The purpose of the writing is to describe the global capitalism against Islamic education. The findings fall into the discussion of factual and real education environmental research on market demand and industrial management (Islamic education contemporary issues). The techniques used in this research are qualitative research at which the data gained from the deep interview and observation. The techniques of data analyses were applied data reduction (data reduction), data description, discussion and drawing conclusion. The principle of capitalism that only seeks profit personal should not be practiced in the world of education. Rising demand of the education accesses will result in the high cost of education. Islamic education institution should not watch out for the jargon